Analysis of Laws and Regulations Regarding the Right to Control Official Housing on State Land - Hermawan, Didy; Holid, Holid; Adrianto, Dedy; Azwar, Irfan; Sufiarina, Sufiarina (Sekolah Pascasarjana Universitas Brawijaya, 2023)
This research analyzes the regulations regarding the right to control official houses on state land based on positive law in Indonesia. The research method used is descriptive-analytic, with thorough data disclosure and explanation as the basis for discussion. The law is reviewed using relevant legal theories and regulations, with descriptive-analytic research as the writing approach. The analysis results explain that state or regional property required to implement government duties cannot be transferred without permission from the Indonesian Regional Representative Council or the Provincial Regional Representative Council. The conclusion is that state or regional property transfer can be done through sale, exchange, donation, or addition as government capital. Still, giving state or regional property to pay off debts with national or regional authorities is prohibited. In addition, granting pledges or utilizing state or regional property as collateral for loans is not allowed. Government regulations set technical and administrative standards for managing state and local property. Keywords: juridical analysis, office house, tenure right